2012
DOI: 10.1177/1468017311434682
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the imbalance between job demands and resources: A study of different coping patterns and implications for health and quality in human service work

Abstract: • Summary:In recent decades the public welfare sector has been subjected to major structural changes, and studies of various occupational groups within human service work have reported increased workload and a high prevalence of work-related stress. Using questionnaire data from a sample of human service workers within social work, child care and elderly care, the aim of this study was to identify different patterns of coping strategies to manage the imbalance between work demands and resources, and then to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 36 publications
(42 reference statements)
1
48
0
5
Order By: Relevance
“…While the outcomes from a multidisciplinary care were generally better than those from a non-cooperative care, the incremental outcomes reduced slightly when the number of specialists exceeded a threshold number. This is because such excessive input of human resources can cause an imbalance in operating multidisciplinary care [29]. In addition, due to the differences in the role and required manpower of each specialist in providing multidisciplinary care, the optimal combinations in a multidisciplinary care team could be different.…”
Section: Discussionmentioning
confidence: 99%
“…While the outcomes from a multidisciplinary care were generally better than those from a non-cooperative care, the incremental outcomes reduced slightly when the number of specialists exceeded a threshold number. This is because such excessive input of human resources can cause an imbalance in operating multidisciplinary care [29]. In addition, due to the differences in the role and required manpower of each specialist in providing multidisciplinary care, the optimal combinations in a multidisciplinary care team could be different.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional design in this study does not allow for any causal conclusions. However, the interpretation of a causal relationship between compensatory strategies and reduced health is theoretically and empirically supported by similar studies (Hockey, 1997;Gustafsson, 2008;Astvik & Melin, 2012). It may of course be discussed to what extent and how statistically significant findings, which in part are a function of sample size, always mirror practically significant results.…”
Section: Practical Implications and Limitationsmentioning
confidence: 83%
“…The coping strategy measurements in the questionnaire derive from a comprehensive research project within the public welfare sector concerning strategies for health and service quality (Astvik & Melin, 2012). The items measure basic and general ways of handling excessive workload.…”
Section: Strategiesmentioning
confidence: 99%
“…Stinchcomb (2004) addresses the impact of organizational stress in police work and considers coping a symptom rather than a cause of an individual's poor mental health. In their narrative study of human service workers, Astvik and Melin (2013) found that compensatory and quality-reducing strategies were risk factors for poor mental health among social workers. Furthermore, social workers used more problem-focused coping strategies in stressful work situations (Ben-Zur & Michael, 2007;Gellis, 2002;Padyab, Ghazinour, & Richter, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%